Examining Tourism Resilience Practices as basis for a Post-Covid 19 Recovery in the Philippines - Joy Sheelah Baraero Era; Johncent Mendoza Del Rosario (Centre For Tourism Planning and Development, 2020)
This study examined the concepts and practices of tourism resilience vis-Ã -vis its vulnerability from shocks and external forces such as natural disasters, climate change, catastrophic events, and virus outbreaks (SARS, Ebola, and recently, the Corona Virus or COVID-19). Espousing a grounded perspective on resilience as emerging from this new phenomenon that is yet to be explored and analyzed, several studies and theories of tourism resilience were reviewed. These are: resilience cycle or